2020
DOI: 10.1016/j.ajp.2020.102218
|View full text |Cite
|
Sign up to set email alerts
|

Ethical standards for telemental health must be maintained during the COVID-19 pandemic

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 9 publications
(13 reference statements)
0
14
0
Order By: Relevance
“…Similar with in-person interventions, clinicians are legally obligated to seek informed consent and review possible risks and benefits of the treatment. 31 Nittari et al 32 recently reviewed legal issues related to informed consent, data protection, confidentiality, physician's malpractice and liability in telemedicine. The main issue reported by the authors is the global uncertainty of the legislation in the field.…”
Section: Privacy and Legal Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar with in-person interventions, clinicians are legally obligated to seek informed consent and review possible risks and benefits of the treatment. 31 Nittari et al 32 recently reviewed legal issues related to informed consent, data protection, confidentiality, physician's malpractice and liability in telemedicine. The main issue reported by the authors is the global uncertainty of the legislation in the field.…”
Section: Privacy and Legal Issuesmentioning
confidence: 99%
“…It has been suggested that clinicians need to update their knowledge and adapt to the newest regulations related to online interventions. 31…”
Section: Privacy and Legal Issuesmentioning
confidence: 99%
“…It should be noted that the attending physician and the psychologist assigned will be able to access physicians' portal via their mobile phone with a username and password. This will ensure the privacy and security of the patient's information and the relevant classified information ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…This research does the intervention online since Indonesia is currently making a Large-Scale Social restrictions regulation (PSBB) in its regions. Online therapy is the perfect alternative to provide mental health services to people during a pandemic [20]. Nevertheless, researcher has not found any research or module regarding self-esteem with the CBT approach done online in Indonesia.…”
Section: Introductionmentioning
confidence: 99%